Validation of the AnyBody full body musculoskeletal model in computing lumbar spine loads at L4L5 level. (14th June 2017) - Bassani, Tito; Stucovitz, Elena; Qian, Zhihui; Briguglio, Matteo; Galbusera, Fabio
Abstract: In the panorama of available musculoskeletal modeling software, AnyBody software is a commercial tool that provides a full body musculoskeletal model which is increasingly exploited by numerous researchers worldwide. In this regard, model validation becomes essential to guarantee the suitability of the model in representing the simulated system. When focusing on lumbar spine, the previous works aimed at validating the AnyBody model in computing the intervertebral loads held several limitations, and a comprehensive validation is to be considered as lacking. The present study was aimed at extensively validating the suitability of the AnyBody model in computing lumbar spine loads at L4L5 level. The intersegmental loads were calculated during twelve specific exercise tasks designed to accurately replicate the conditions during which Wilke et al. (2001) measured in vivo the L4L5 intradiscal pressure. Motion capture data of one volunteer subject were acquired during the execution of the tasks and then imported into AnyBody to set model kinematics. Two different approaches in computing intradiscal pressure from the intersegmental load were evaluated. Lumbopelvic rhythm was compared with reference in vivo measurements to assess the accuracy of the lumbopelvic kinematics. Positive agreement was confirmed between the calculated pressures and the in vivo measurements, thus demonstrating the suitability of the AnyBody model. Specific caution needs to be taken only when considering postures characterized by large lateral displacements. Minor discrepancy was found assessing lumbopelvic rhythm. The present findings promote the AnyBody model as an appropriate tool to non-invasively evaluate the lumbar loads at L4L5 in physiological activities.